IgG2 rules: N-acetyl-β-D-glucosamine-specific IgG2 and Th17/Th1 cooperation may promote the pathogenesis of acute rheumatic heart disease and be a biomarker of the autoimmune sequelae of Streptococcus pyogenes - Kirvan, Christine A.; Canini, Heather; Swedo, Susan E.; Hill, Harry; Veasy, George; Jankelow, David; Kosanke, Stanley; Ward, Kent; Zhao, Yan D.; Alvarez, Kathy; Hedrick, Andria; Cunningham, Madeleine W. (Frontiers in Cardiovascular Medicine, 2023)
Antecedent group A streptococcal pharyngitis is a well-established cause of acute rheumatic fever (ARF) where rheumatic valvular heart disease (RHD) and Sydenham chorea (SC) are major manifestations. In ARF, crossreactive antibodies and T cells respond to streptococcal antigens, group A carbohydrate, N-acetyl-β-D-glucosamine (GlcNAc), and M protein, respectively, and through molecular mimicry target heart and brain tissues. In this translational human study, we further address our hypothesis regarding specific pathogenic humoral and cellular immune mechanisms leading to streptococcal sequelae in a small pilot study. The aims of the study were to (1) better understand specific mechanisms of pathogenesis in ARF, (2) identify a potential early biomarker of ARF, (3) determine immunoglobulin G (IgG) subclasses directed against GlcNAc, the immunodominant epitope of the group A carbohydrate, by reaction of ARF serum IgG with GlcNAc, M protein, and human neuronal cells (SK-N-SH), and (4) determine IgG subclasses deposited on heart tissues from RHD. In 10 pediatric patients with RHD and 6 pediatric patients with SC, the serum IgG2 subclass reacted significantly with GlcNAc, and distinguished ARF from 7 pediatric patients with uncomplicated pharyngitis. Three pediatric patients who demonstrated only polymigrating arthritis, a major manifestation of ARF and part of the Jones criteria for diagnosis, lacked the elevated IgG2 subclass GlcNAc-specific reactivity. In SC, the GlcNAc-specific IgG2 subclass in cerebrospinal fluid (CSF) selectively targeted human neuronal cells as well as GlcNAc in the ELISA. In rheumatic carditis, the IgG2 subclass preferentially and strongly deposited in valve tissues (n = 4) despite elevated concentrations of IgG1 and IgG3 in RHD sera as detected by ELISA to group A streptococcal M protein. Although our human study of ARF includes a very small limited sample set, our novel research findings suggest a strong IgG2 autoantibody response against GlcNAc in RHD and SC, which targeted heart valves and neuronal cells. Cardiac IgG2 deposition was identified with an associated IL-17A/IFN-γ cooperative signature in RHD tissue which displayed both IgG2 deposition and cellular infiltrates demonstrating these cytokines simultaneously. GlcNAc-specific IgG2 may be an important autoantibody in initial stages of the pathogenesis of group A streptococcal sequelae, and future studies will determine if it can serve as a biomarker for risk of RHD and SC or early diagnosis of ARF.